POSTGRADUATE STUDENT OF THE 2010S: A SOCIOLOGICAL PORTRAIT - Y. S. Shirokova (Вестник университета)
Currently, much attention in the field of higher education is paid to the problems of the third stage – postgraduate education. The main problems are: reducing the awarding of scientific degrees, decreasing the reproduction of the personnel capacity of higher school and scientific activities. The purpose of the paper is to study the trajectories of postgraduate education, based on the data of empirical research “Professional trajectories of postgraduate students” at the Dubna State University and at the “National Research University “Higher School of Economics”. The main methods were a sociological survey and analysis of secondary information. Based on the results of the study, a portrait of a modern postgraduate student has been compiled. Two identical studies produced mostly different results. This suggests that there is a need for such research.